Synthesis of Carboxylic Acid by 2-Hexenal Oxidation Using Gold Catalysts Supported on MnO2 - Hamed Alshammari (Journal of Chemistry)
Synthesis of carboxylic acid can be achieved by the oxidation of aldehyde using air as an oxidant in the presence of a potential catalyst. We demonstrated that 2-hexenal can be oxidized to carboxylic acid by Au, Pd, and Au-Pd catalysts and investigated the effects of catalyst support (graphite, TiO2, MgO, SiC, MnO2, CeO2, and Al2O3), preparation method for supported catalyst (sol immobilization, impregnation, and deposition precipitation), and choice of catalyst components. Analysis of conversion% and selectivity% for 2-hexenoic acid showed that MnO2-supported gold nanoparticles are the best catalysts for 2-hexenal oxidation. Moreover, catalysts prepared by sol immobilization are the most active possibly due to the much smaller gold nanoparticle size. Selectivity for 2-hexenoic acid is a major pathway of oxidation of 2-hexenal.